2018
DOI: 10.7150/ijms.22410
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MiR-203a Disinhibits Bmi1 and Promotes Growth and Proliferation of Keratinocytes in Cholesteatoma

Abstract: Background: Keratinocytes are the predominant cell type in a cholesteatoma, and microRNA (miR)-203a has been shown to be essential for the growth and differentiation of keratinocytes. The regulatory mechanisms of miR-203a and Bmi1—the predicted target of miR-203a that is associated with cholesteatoma—have not been clarified.Methods: Real-time PCR and western blot were carried out for the detection of miRNAs, mRNAs, and proteins, including miR-203a, Bmi1, and phosphorylated (p-)Akt. Immunohistochemical staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Some reports have shown that lncRNA ANRIL is associated with osteosarcoma and lung cancer; 4 , 5 however, the role of lncRNA ANRIL in glioma has not been fully elucidated. An increased expression of lncRNA ANRIL in glioma correlating with grade and a negative correlation with the anti-oncogene miR-203a has been found; 6 , 7 thus, we considered that there may be a potential relationship between lncRNA ANRIL, the glioma tumorigenesis process, and miR-203a expression. This study aimed to explore the effect of lncRNA ANRIL silencing on induced anoikis and cell cycle arrest in human glioma and the possible mechanism involved.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown that lncRNA ANRIL is associated with osteosarcoma and lung cancer; 4 , 5 however, the role of lncRNA ANRIL in glioma has not been fully elucidated. An increased expression of lncRNA ANRIL in glioma correlating with grade and a negative correlation with the anti-oncogene miR-203a has been found; 6 , 7 thus, we considered that there may be a potential relationship between lncRNA ANRIL, the glioma tumorigenesis process, and miR-203a expression. This study aimed to explore the effect of lncRNA ANRIL silencing on induced anoikis and cell cycle arrest in human glioma and the possible mechanism involved.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs have vital functions in regulating cellular activities. Over the past years, substantial studies have confirmed the involvement of miRNA in the pathogenesis of acquired cholesteatoma [ 11 , 14 , 26 ]. Notably, miR-199a has attracted wide attention.…”
Section: Discussionmentioning
confidence: 99%
“…2020-KY-225) for the whole research, as well as all involved patients' (or their parents') written informed consent, was obtained before the research. Cholesteatoma tissues and matched normal postauricular skin tissues [ 11 , 21 , 22 ] were obtained from cholesteatoma patients conformed by pathologists in the First Affiliated Hospital of Zhengzhou University from March 2020 to June 2020. The collected specimens were sent to the laboratory for immediate surgery.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations